Molecular-frame differential photoelectron circular dichroism of O 1s-photoelectrons of trifluoromethyloxirane - G. Nalin; N. M. Novikovskiy; K. Fehre; N. Anders; D. Trabert; S. Grundmann; M. Kircher; A. Khan; R. Tomar; M. Hofmann; M. Waitz; I. Vela-Perez; et al. (Physical Review Research, 2023)
The differential photoelectron circular dichroism (PECD) of O 1s photoelectrons of R-trifluoromethyloxirane enantiomers as a function of the photoelectron emission direction in the molecular frame of reference and the direction from which circularly polarized light hits the molecule, is studied experimentally and theoretically for different photoelectron kinetic energies. A coincident detection of the photoelectrons and two ionic molecular fragments, performed with cold target recoil ion momentum spectroscopy, allows us to determine the orientation of the molecule in the laboratory frame and to obtain in addition the molecular-frame photoelectron diffraction patterns. From these we deduce the differential PECD. For given molecular orientations and photoelectron emission directions, we observe a normalized PECD strength clearly beyond 50%. These observations are in agreement with respective relaxed-core Hartree-Fock calculations, performed by employing the single center method. The present results support our recent observation of a huge differential PECD in O 1s photoemission of the methyloxirane molecule.